Identification of a second kindred with familial hypocalciuric hypercalcemia type 3 (FHH3) narrows localization to a <3.5 megabase pair region on chromosome 19q13.3. - Nesbit, M; Hannan, F; Graham, U; Whyte, M; Morrison, P; Hunter, S; Thakker, R (2010)
CONTEXT: Familial hypocalciuric hypercalcemia (FHH) is a genetically heterogenous disorder that consists of three defined types, FHH1, FHH2, and FHH3 whose chromosomal locations are 3q21.1, 19p, and 19q13, respectively. FHH1, caused by mutations of the calcium-sensing receptor (CASR), occurs in more than 65% of patients, whereas the abnormalities underlying FHH2 and FHH3, which have each been described in single North American kindreds, are unknown. OBJECTIVE: The aim of this study was to determine the basis of FHH in a proband, who did not have CASR mutations, and her kindred. PATIENTS AND METHODS: The proband was a 43-yr-old woman who presented with a corrected serum calcium of 2.74 mmol/liter (normal = 2.15-2.55 mmol/liter), a serum PTH of 47 pg/ml (normal = 10-65 pg/ml), and a urinary calcium clearance:creatinine clearance of 0.006. She did not have a CASR mutation within the coding region and splice sites, and 24 members from three generations of her kindred were ascertained and investigated for serum abnormalities and cosegregation with polymorphic loci from chromosomes 3q21.1 and 19q13 using leukocyte DNA. RESULTS: Sixteen members were hypercalcemic with normal or elevated serum PTH concentrations and mild hypophosphatemia, features consistent with FHH3. Use of microsatellite and single nucleotide polymorphic loci from chromosome 19q13.3 demonstrated cosegregation with FHH in the kindred, with a peak LOD score = 5.98 at 0% recombination with D19S412. Analysis of recombinants mapped FHH to a 3.46-Mbp interval flanked centromerically by single nucleotide polymorphism rs1990932 and telomerically by D19S604. CONCLUSIONS: FHH3 may explain the calcium homeostasis disorder in those FHH patients who do not have CASR mutations.